Strategi Komunikasi Tengku Achmad Thala'a Selama Menjadi DPRD Deli Serdang - Syauqii, Fachri; Majid, Nurjulian (Medan Resource Center, 2022)
This research aims to analyze the communication strategies implemented by Tengku Achmad Thala'a during his tenure as a member of the Regional People's Representative Council (DPRD) of Deli Serdang. The method used in this research is qualitative with a case study approach, where data was obtained through in-depth interviews, observations, and analysis of relevant documents. The results of the study indicate that Tengku Achmad Thala'a implemented various effective communication strategies in performing his duties and functions. These strategies include the use of social media for direct interaction with constituents, organizing discussion forums and policy socialization at the local level, and collaborating with various stakeholders to enhance transparency and public participation. Additionally, good interpersonal communication skills and an inclusive approach to absorbing community aspirations were key to building harmonious relationships with various parties. This research concludes that appropriate and effective communication strategies play a significant role in improving the performance and credibility of a DPRD member in the public eye.